Induction and Aggravation of the Endoplasmic-Reticulum Stress by Membrane-Lipid Metabolic Intermediate Phosphatidyl-N-Monomethylethanolamine - Ishiwata-Kimata, Yuki; Le, Quynh Giang; Kimata, Yukio (Frontiers in Cell and Developmental Biology, 2022)
Phosphatidylcholine (PC) is produced via two distinct pathways in both hepatocytes and yeast, Saccharomyces cerevisiae. One of these pathways involves the sequential methylation of phosphatidylethanolamine (PE). In yeast cells, the methyltransferase, Cho2, converts PE to phosphatidylmonomethylethanolamine (PMME), which is further modified to PC by another methyltransferase, Opi3. On the other hand, free choline is utilized for PC production via the Kennedy pathway. The blockage of PC production is well known to cause endoplasmic reticulum (ER) stress and activate the ER-stress sensor, Ire1, to induce unfolded protein response (UPR). Here, we demonstrate that even when free choline is sufficiently supplied, the opi3Delta mutation, but not the cho2Delta mutation, induces the UPR. The UPR was also found to be induced by CHO2 overexpression. Further, monomethylethanolamine, which is converted to PMME probably through the Kennedy pathway, caused or potentiated ER stress in both mammalian and yeast cells. We thus deduce that PMME per se is an ER-stressing molecule. Interestingly, spontaneously accumulated PMME seemed to aggravate ER stress in yeast cells. Collectively, our findings demonstrate the multiple detrimental effects of the low-abundance phospholipid species, PMME.